Effects of psychological interventions on anxiety and pain in patients undergoing major elective abdominal surgery: a systematic review - Gianluca Villa; Iacopo Lanini; Timothy Amass; Vittorio Bocciero; Caterina Scirè Calabrisotto; Cosimo Chelazzi; Stefano Romagnoli; A. Raffaele De Gaudio; Rosapia Lauro Grotto (Perioperative Medicine, 2020)
Abstract A maladaptive response to surgical stress might lead to postoperative complications. A multidisciplinary approach aimed at controlling the surgical stress response may reduce procedural complications and improve patients’ quality of life in the short and long term. Several studies suggest that psychological interventions may interact with the pathophysiology of surgical stress response, potentially influencing wound repair, innate and adaptive immunity, inflammation, perception of pain, and patients’ mood. The aim of this systematic review is to summarise the effects of perioperative psychological interventions on surgical pain and/or anxiety in adult patients scheduled for elective general abdominal and/or urologic surgery. We conducted a systematic review of controlled clinical trials and observational studies involving psychological interventions for adult patients scheduled for elective general abdominal and/or urologic surgery. Only studies reporting pain and/or anxiety among outcome measures were included in the systematic review. The following psychological interventions were considered: (1) relaxation techniques, (2) cognitive-behavioural therapies, (3) mindfulness, (4) narrative medicine, (5) hypnosis and (6) coping strategies. We examined 2174 papers. Among these, 9 studies were considered eligible for inclusion in this systematic review (1126 patients cumulatively): 8 are randomised controlled trials and 1 is an observational prospective pre/post study. Psychological characteristics widely influence the pathophysiological mechanisms underlying the neuroendocrine and inflammatory response to surgical stress, potentially interfering with surgical outcomes. Psychological interventions are technically feasible and realistically applicable perioperatively during abdominal and/or urologic surgery; they influence the pathophysiological mechanisms underlying maladaptive surgical stress response and might have positive effects on patients’ surgical outcomes, such as pain and anxiety.